KESULITAN BELAJAR NOTASI LABAN BAGI MAHASISWA PROGRAM STUDI PENDIDIKAN TARI UNIVERSITAS LAMPUNG - Marsanda Putri, Dera; Habsary, Dwiyana; Gustia Ningsih, Lora (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning difficulties of students of the Dance Education Study Program, class of 2022, University of Lampung in understanding Laban Notation in the Dance Documentation course. The study used a descriptive qualitative method with 29 students and one lecturer as subjects. Data were collected through observation, interviews, and document studies, then analyzed using data reduction, data presentation, and conclusion drawing. The results of the study showed that students had difficulty reading symbols for direction, level, support, and rotation, as well as converting symbols into movements. In the writing aspect, students still made mistakes in writing symbols for direction, level, support, rotation, and symbol completeness. In the counting aspect, some students still had difficulty adjusting calculations to changes in movement. The results of the ability test showed that only 1 of 29 students was able to read Laban Notation well through Lenggang movement practice, the others were almost correct and good, while 10 students were able to write movements into Laban Notation through Tahtim movement well. Based on the research results, it can be concluded that difficulties in learning Laban Notation among students include the ability to read, write and calculate which are interrelated so that they are included in academic learning difficulties in the form of dyslexia, dysgraphia and dyscalculia.